2001
DOI: 10.1088/0957-0233/12/8/306
|View full text |Cite
|
Sign up to set email alerts
|

The design of a dual-plane ERT system for cross correlation measurement of bubbly gas/liquid pipe flow

Abstract: Combining electrical resistance tomography (ERT) with the cross-correlation flow measurement technique can provide more information on the flow than usual. A dual-plane ERT system for use on laboratory-and plant-scale process equipment has been developed on the basis of this idea. This paper focuses on the design of it. The principle of measurement of the local gas velocity distribution in a bubbly gas/liquid pipe flow based on pixel-pixel cross correlation of two plane images is described. Methods to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…EIT may, therefore, be suitable for numerous aqueous-based processes (York 2001). Using sequences of images obtained from a dual-plane EIT flow sensor, the local flow velocity of the dispersed phase(s) can be deduced based on pixel-pixel cross-correlation methods (Lucas et al 1999, Deng et al 2001, Mosorov et al 2002. This demands an EIT system to have a rapid response time (Wang et al 2005) in order to measure multiphase flows with phase distributions changing in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…EIT may, therefore, be suitable for numerous aqueous-based processes (York 2001). Using sequences of images obtained from a dual-plane EIT flow sensor, the local flow velocity of the dispersed phase(s) can be deduced based on pixel-pixel cross-correlation methods (Lucas et al 1999, Deng et al 2001, Mosorov et al 2002. This demands an EIT system to have a rapid response time (Wang et al 2005) in order to measure multiphase flows with phase distributions changing in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…The flow regime describes the pattern of the inner structure of the flow and important hydrodynamic features such as volume fraction, phase and velocity distributions. Two phase flow regimes are often determined subjectively using direct methods such as the eyeballing method, high speed photography method and the radial attenuation method [12]. Empirical flow regime maps such as the Baker chart [2,34] are commonly used for approximate and rapid identification of the flow regime under specific operating conditions.…”
Section: Classification and Applicationsmentioning
confidence: 99%
“…At home, in 2001, Tianjin university's research team, led by professor huaxiang wang, developed the TERT -1, 2, 3, 4 type system prototype, under the system of gas liquid two phase flow and oil/water two phase flow in a lot of kinds of experimental research, concluded that ERT acquisition system can realize two phase flow detection and the specific flow pattern identification of two phase flow [9]. In 2007, tianjin university zi qiang cui and others designed a kind of excitation signal source based on the FPGA implementation without touching the hardware circuit, can realize the signal frequency, amplitude, phase Angle, change type, can meet the demand of different data acquisition mode of ERT system.…”
Section: Condition Monitoring and Its Parameters Of Multiphase Flow Mmentioning
confidence: 99%